Correlation of selective serotonin re-uptake inhibitor use with weight gain and metabolic parameters - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2013)
Objective: Psychotropic drugs during the treatment period of psychiatric disorders can cause changes in metabolic parameters such as weight, lipid profile, fasting glucose level, and resting metabolic rate. The aim of this study is to investigate the correlation of selective serotonin re-uptake inhibitor (SSRI) use with weight gain and metabolic parameters. Methods: In this study, the resting metabolic rates (RMR) of 14 male patients intended to use selective serotonin re uptake inhibitor at least three months, were measured baseline, first and third month after SSRI use. Body weight, percentage body fat, body mass index and waist/hip ratio were measured before treatment, at the end of the first and second weeks and the first, second and third months. Laboratory tests including total cholesterol, LDL, HDL, VLDL, triglycerides and fasting blood glucose were performed before treatment and at the end of the third month. The correlation of body weight changes with RMR changes was also analyzed. Results: RMR did not differ in the beginning, first month and third month. No statistically significant difference was found in RMR between the beginning and the third month. RMR significantly decreased in the increased-dose group while it wasn't changed in the constant-dose group. No correlation was found between RMR changes and body weight changes. The mean body weight decreased significantly between the beginning and the first week and the first month. Even though the mean body weight of all patients was higher in the third month than the beginning, no statistically significant difference was found. The total cholesterol levels, body lipid ratio, and waist/hip ratio increased significantly between initiation of treatment and the third month. Conclusion: As a result, we suggest that SSRI's use did not cause body weight increase due to reduction in RMR. The waist/hip ratio, total cholesterol levels were increased in the third month. Further studies which look more closely to fat metabolism in patients under SSRI's treatment are necessary.
Keywords: Selective serotonin re uptake inhibitor; resting metabolic rate; body weight; metabolic parameters; DEPRESSION SCALE; MECHANISMS; MANAGEMENT